2020
DOI: 10.15835/nbha48312004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on in vitro micropropagation response of seven globe artichoke [Cynara cardunculus var. scolymus (L.) Fiori] cultivars: open-pollinated cultivars vs F1 hybrids

Abstract: Globe artichoke [Cynara cardunculus var. scolymus (L.) Fiori] growing has gained commercial importance in recent years due to its consumption as food. It has also started to attract attention in pharmaceutics. Due to globe artichoke’s stated importance, growers need large amount of pathogen-free, healthy starting materials for production. Stated material will maximize the yield while minimizing the costs. Hybrid cultivars have uniform in height and maturity and could be harvested concurrently; on the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In the present research, such as already tested in several different artichoke genotypes [9,19,40,41], the addition of IAA at high concentration (10 mg L −1 ), in combination with the increase in sucrose concentration from 20 to 30 g L −1 allowed us to achieve a satisfactory percentage of rooting and a root system characterized by a strong root length of 4.5 cm at the moment of plantlet transplanting into greenhouse. The same concentration of IAA was also applied to induce rooting by Ozsan and Onus [38,42] on open-pollinated cultivars and F1 hybrids and Tavazza et al [43] on cv. Spinoso Sardo.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, such as already tested in several different artichoke genotypes [9,19,40,41], the addition of IAA at high concentration (10 mg L −1 ), in combination with the increase in sucrose concentration from 20 to 30 g L −1 allowed us to achieve a satisfactory percentage of rooting and a root system characterized by a strong root length of 4.5 cm at the moment of plantlet transplanting into greenhouse. The same concentration of IAA was also applied to induce rooting by Ozsan and Onus [38,42] on open-pollinated cultivars and F1 hybrids and Tavazza et al [43] on cv. Spinoso Sardo.…”
Section: Discussionmentioning
confidence: 99%
“…scolymus L.) germplasm for inulin with a high degree of polymerization in the Mediterranean environment, to reduce breeding time and offer growers uniform, healthy globe artichoke plants. Ozsan and Onus [ 82 ] compared in vitro micropropagation response of open-pollinated cultivars with F1 hybrids in maturity and height. They concluded that open-pollinated cultivars are cheaper than F1 and could be used for in vitro mass propagation.…”
Section: Micropropagation Of Plants For Production Of Large Therapmentioning
confidence: 99%